A Framework of Strategies to Mitigate the Frequency and Impact of Human-Elephant Conflicts in the Game Reserve Areas of Zimbabwe - Nunurai, Gutu; Walter, Musakwa; Sydney, Togarepi (Indonesian Journal of Community Services, 2025)
This study examined a framework of strategies to mitigate the frequency and impact of Human Elephant Conflicts (HEC) in the Game Reserve areas of Zimbabwe. The research was conducted specifically in Malipati, a lowveld area of Zimbabwe. In explaining the study, researchers used the social ecological theory by Berkes and Folke, (1998). Researchers employed a mixed-methods approach, combining a cross-sectional survey. The target population were Zimparks personnel, community members, and local leaders. The study's population was estimated to be 142. This implied that according to the Krejcie and Morgan’s sample size determination the sample size became 105. The analysis of quantitative data was done using SPSS version 23 software whilst qualitative data was analysed using NVivo version 12. The research found that strategies that includes educational outreach programs, compensation schemes for property damage, fencing initiatives, and the use of deterrents like alarms and scarecrows may be used to mitigate the frequency and impact of Human-Elephant Conflicts in the Game Reserve areas of Zimbabwe. Study recommended that government ensure compensation schemes for victims of HEC that are fair and transparent.